Meta-affective progression in science: A cross-sectional study of junior high school students - Pipih Nurhayati; Ari Widodo; Widi Purwianingsih; Achmad Samsudin (Acta Psychologica, 2025)
The Programme for International Student Assessment (PISA), a global benchmark for science education, reported stagnation in student achievement worldwide. While some Asian nations excel, their emphasis on cognitive achievement puts high emotional pressure on students. This study investigated the progression of meta-affective skills in science education across the junior high school years by comparing students in the 7th and 9th grades from two cities in West Java, Indonesia. The research employed a developmental study methodology using a cross-sectional design. Two hundred participants were involved, evenly divided between the two grades. Meta-affective traits were assessed using the Meta-Affective Traits for Science Young Learners (MATSYL) questionnaire, comprising 26 statements rated on a five-point Likert scale, measuring two leading indicators: awareness of affect and regulation of affect. Data analysis employed the Independent Samples T-Test, Percentage Change, and Annual Growth Rate. Results revealed significant differences between 7th and 9th grade students across four sub-indicators: awareness of positive affect, awareness of negative affect, expression of positive affect, and expression of negative affect. The 9th-grade students consistently exhibited higher mean scores in all four sub-indicators than their 7th-grade counterparts. These findings suggest a progression in meta-affective growth as students advance through junior high school, particularly in their ability to recognize and express positive and negative emotions in science learning contexts. However, the two groups are not different in expressing and regulating negative affect. This development study provides valuable insights into students' affective development trajectory in science education throughout the junior high school years, thereby enhancing our understanding of meta-affective growth in academic settings.